Sistem Pendukung Keputusan Pemilihan Peserta Olimpiade Karya Ilmiah Tingkat Nasional Menggunakan Metode SAW - Achmad Fikri Sallaby; Venny Novita Sari; Rizka Tri Alinse (Universitas Budi Darma, 2021)
Participants of the national level scientific work olympic are participants who will take part in competitions between one campus and another on a national basis in showing scientific works or research results with certain themes in a competition. The importance of choosing is because an olympic participant is a pride and also brings the good name of the college where they study, if you bring the wrong participant it will create new problems in assessing the quality of a university, in this study, the selection of participants for the olympic scientific work at the national level using concept of the algorithm of a decision support system using the MOORA method. The MOORA method or the abbreviation of Multi-Objective Optimization on The Basis Of Ratio Analysis is a decision support system method that has simple stages and processes in solving problems. The results of this study found the highest score with the candidate with a value of 10.93991.